Le Livre des Haltes (Kitâb al-Mawâqif), Tome I - Lagarde, Michel (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This first of three volumes comprising 'Abd al Qâdir's work contains 215 of the 372 original chapters. Based on the Dār al-yaqaza al-'arabiyya (1966-1967) and on the manuscript of the Library of Alger, this translation addresses the work done so far by Michel Chodkiewicz and by A. Khurshīd. It deals with mystic comments on Qur'anic verses and prophetic translations inspired by Ibn 'Arabi's work. It serves as a useful introduction to Futuḥāt and Fusus .